2020
DOI: 10.1002/adma.202000186
|View full text |Cite
|
Sign up to set email alerts
|

High Phase Stability in CsPbI3 Enabled by Pb–I Octahedra Anchors for Efficient Inorganic Perovskite Photovoltaics

Abstract: CsPbI3 inorganic perovskite has exhibited some special properties particularly crystal structure distortion and quantum confinement effect, yet the poor phase stability of CsPbI3 severely hinders its applications. Herein, the nature of the photoactive CsPbI3 phase transition from the perspective of PbI6 octahedra is revealed. A facile method is also developed to stabilize the photoactive phase and to reduce the defect density of CsPbI3. CsPbI3 is decorated with multifunctional 4‐aminobenzoic acid (ABA), and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 44 publications
0
72
0
1
Order By: Relevance
“…Wheeler et al have shown that the incorporation of oleylammonium (OA + ) processing stabilizes the CsPbI 3 perovskite in the cubic α‐phase whereas the use of PEA + additives stabilizes the CsPbI 3 perovskite in the tetragonal β‐phase where the octahedra are slightly tilted. [ 96 ] The transformation related to the [PbI 6 ] 4− rotation was also shown in the study of Wang et al [ 92 ] Through a surface capping with 4‐aminobenzoic acid, the designated angles between PbI 6 octahedra are 111.20° and 73.93°, being closer to ideal 90° for cubic phase, respectively. However, the corresponding angles on Cs‐terminated surface are 113.83° and 65.15°, respectively.…”
Section: Fabrication and Stabilization Of Cspbi3mentioning
confidence: 63%
See 3 more Smart Citations
“…Wheeler et al have shown that the incorporation of oleylammonium (OA + ) processing stabilizes the CsPbI 3 perovskite in the cubic α‐phase whereas the use of PEA + additives stabilizes the CsPbI 3 perovskite in the tetragonal β‐phase where the octahedra are slightly tilted. [ 96 ] The transformation related to the [PbI 6 ] 4− rotation was also shown in the study of Wang et al [ 92 ] Through a surface capping with 4‐aminobenzoic acid, the designated angles between PbI 6 octahedra are 111.20° and 73.93°, being closer to ideal 90° for cubic phase, respectively. However, the corresponding angles on Cs‐terminated surface are 113.83° and 65.15°, respectively.…”
Section: Fabrication and Stabilization Of Cspbi3mentioning
confidence: 63%
“…Reproduced with permission. [ 92 ] Copyright 2020, Wiley‐VCH. b) Mechanism of the OTG‐induced phase stabilization of CsPbI 3 perovskite.…”
Section: Fabrication and Stabilization Of Cspbi3mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 87,88 ] Recently, Wang et al combined 4‐aminobenzoic acid incorporation with neostigmine bromide surface modification in CsPbI 3 film fabrication, which stabilized the black phase by suppressing PbI 6 octahedral rotation and reducing surface energy. [ 89 ] The modified film kept unchanged in 80% RH air for 2 h or at 80 °C in N 2 for 360 h, in stark contrast to the control CsPbI 3 film which completely turned yellow under the same aging conditions. The champion device delivered a high PCE of 18.27% and the encapsulated cells showed no obvious decay in efficiencies after 200 h storage in a 60% RH under dark conditions.…”
Section: Beyond Perfect Crystals: Surface Strain and Defectmentioning
confidence: 99%